Moderate traumatic brain injury triggers long-term risks for the development of peripheral pain sensitivity and depressive-like behavior in mice - Stelfa, Gundega; Svalbe, Baiba; Vavers, Edijs; Duritis, Ilmars; Dambrova, Maija; Zvejniece, Liga (Frontiers in Neurology, 2022)
As traumatic brain injury (TBI) is one of the major causes of permanent disability, there is increasing interest in the long-term outcome of TBI. While motor deficits, cognitive impairment and longer-term risks of neurodegenerative disease are well-established consequences in animal models of TBI, pain is discussed less often despite its high prevalence. The current study addresses the need to characterize the extent of chronic pain and long-term behavioral impairments induced by moderate lateral fluid percussion injury (latFPI) in mice up to 12 months post-TBI and evaluates the validity of the model. Adult male BALB/c mice were subjected to latFPI, and the results were compared with outcomes in sham-operated mice. Mouse behavior was assessed at 1 and 7 days and 1, 3, 6, 9 and 12 months postinjury using sensory-motor (neurological severity score, NSS), cold (acetone) and mechanical sensitivity (von Frey), depressive-like behavior (tail suspension), locomotor (open field), motor coordination (rotarod) and cognitive (Morris water maze, y-maze, passive avoidance) tests. Animals with TBI demonstrated significantly higher NSS than the sham-operated group for up to 9 months after the injury. Cold sensitization was significantly increased in the contralateral hind paw in the TBI group compared to that of the sham group at 3, 6 and 9 months after TBI. In the von Frey test, the withdrawal threshold of the contralateral and ipsilateral hind paws was reduced at six months after TBI and lasted for up to 12 months postinjury. latFPI induced progressive depressive-like behavior starting at 6 months postinjury. No significant deficits were observed in memory, motor coordination or locomotion over the 12-month assessment period. The present study demonstrates that moderate TBI in mice elicits long-lasting impairment of sensory-motor function, results in progressive depression and potentiates peripheral pain. Hence, the latFPI model provides a relevant preclinical setting for the study of the link between brain injury and chronic sequelae such as depression and peripheral pain.